2023
DOI: 10.3390/ijms242015257
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase USP17 Regulates Osteoblast Differentiation by Increasing Osterix Protein Stability

Myeong Ji Kim,
Meiyu Piao,
Yuankuan Li
et al.

Abstract: Deubiquitinases (DUBs) are essential for bone remodeling by regulating the differentiation of osteoblast and osteoclast. USP17 encodes for a deubiquitinating enzyme, specifically known as ubiquitin-specific protease 17, which plays a critical role in regulating protein stability and cellular signaling pathways. However, the role of USP17 during osteoblast differentiation has not been elusive. In this study, we initially investigated whether USP17 could regulate the differentiation of osteoblasts. Moreover, USP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…DUBs play an important role in bone remodeling by regulating osteoblasts and osteoclasts, and STAMBP/AMSH is an important subtype in JAMMs. 55 Studies showed that STAMBP can increase NACHT, LRR and PYD domains‐containing protein 7 (NALP7) inflammasome and IL‐1β levels to promote inflammation through deubiquitination. 56 On the other hand, we discovered that STAMBP could raise the risk of spondylolisthesis/spondylolysis.…”
Section: Discussionmentioning
confidence: 99%
“…DUBs play an important role in bone remodeling by regulating osteoblasts and osteoclasts, and STAMBP/AMSH is an important subtype in JAMMs. 55 Studies showed that STAMBP can increase NACHT, LRR and PYD domains‐containing protein 7 (NALP7) inflammasome and IL‐1β levels to promote inflammation through deubiquitination. 56 On the other hand, we discovered that STAMBP could raise the risk of spondylolisthesis/spondylolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, members of the Casitas B-lineage lymphoma family, Cbl-b and c-Cbl, have been identified as regulators that diminish the protein stability of Osx during BMP2-induced osteoblast differentiation through ubiquitin–proteasome-mediated degradation 342 . More recently, ubiquitin-specific protease 17 (USP17) has been found to increase Osx protein levels via modulating deubiquitylation, positively impacting osteoblast differentiation as evidenced by enhanced alkaline phosphatase (ALP) expression and activity 343 . These findings open a novel avenue for direct intervention and manipulation of Osx stability, providing a potential approach to enhance or inhibit osteoblast differentiation.…”
Section: Osteoblast Transcriptional Factorsmentioning
confidence: 99%